Food insecurity as measured by individual perceptions - Corrêa, Ana Maria Segall (Estudos Avançados, 2007)
This paper brings the validation process of the Brazilian Scale to measure food insecurity (Ebia), which has been conducted from 2003 through 2004. It was a collaborative study that took place in five Brazilian States and was carried out initially with a qualitative method, bringing up the opinion of four specialists panels and also eleven focus groups to evaluate the comprehension of concepts by participants living in poor communities. The second phase comprised five surveys that used convenience samples of different social strata of the population. The high understanding of the study population about the scale concepts and contents is emphasized, showing its adequacy to Brazilian reality, meaning that the country can now rely on an instrument to direct measuring food insecurity and hunger with high internal and external validity, easy to use and of low cost application.